2015
DOI: 10.5455/msm.2015.27.180-184
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility/Resistance of Streptococcus Pneumoniae

Abstract: Introduction:Pneumococcal infections are a major cause of morbidity and mortality worldwide, whose treatment is threatened with an increase in the number of strains resistant to antibiotic therapy.Goal:The main goal of this research was to investigate the presence of antimicrobial susceptibility/resistance of S. pneumoniae.Material and methods:Taken are swabs of the nose and nasopharynx, eye and ear. In vitro tests that were made in order to study the antimicrobial resistance of pneumococci are: disk diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
1
15
1
Order By: Relevance
“…This is similar to the results obtained by Kandakai and Dido (2009) [5] who demonstrated that Streptococcus pneumoniae isolated from the pharynx was highly resistance to erythromycine and tetracycline, but susceptible to ciproflolaxcine. These results are also similar to those obtained by Emina et al, (2015) [29], when studying the antimicrobial susceptibility/resistance of S. pneumoniae isolated from the eyes, resistance was highest to erythromycine and lowest at ciproflolaxcine. Multi drug resistance was also noted in Streptococcus pneumoniae (tetracycline; aminoglycosides; netilimcin; Β-lactam; ceftazidime;…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to the results obtained by Kandakai and Dido (2009) [5] who demonstrated that Streptococcus pneumoniae isolated from the pharynx was highly resistance to erythromycine and tetracycline, but susceptible to ciproflolaxcine. These results are also similar to those obtained by Emina et al, (2015) [29], when studying the antimicrobial susceptibility/resistance of S. pneumoniae isolated from the eyes, resistance was highest to erythromycine and lowest at ciproflolaxcine. Multi drug resistance was also noted in Streptococcus pneumoniae (tetracycline; aminoglycosides; netilimcin; Β-lactam; ceftazidime;…”
Section: Discussionsupporting
confidence: 92%
“…Although overall frequency of doxycycline resistance in S. pneumoniae in 2004 was 24%, rates vary widely geographically and over time, and may range from 2% to more than 20%, and more than 60% in penicillin-resistant strains, potentially limiting the use of doxycycline for more severe pneumococcal infections. [34][35][36][37] In our study, the prevalence of pneumonia in subjects tested during wave 1 was 23% overall, but 36% in Q fever positive subjects, which is higher than the 27% rate found in Q fever positive patients from a large 26-year cohort of patients with Q fever from the French National Reference Center for Q fever. [38] Nevertheless, a huge majority of patients in our study had no suspicion of pneumonia and would have had potential bene t from symptom-based exclusion of Q fever.…”
Section: Discussionmentioning
confidence: 79%
“…Although overall frequency of doxycycline resistance in S. pneumoniae in 2004 was 24%, rates vary widely geographically and over time, ranging from 2% to more than 20%, and more than 60% in penicillin-resistant strains, potentially limiting the use of doxycycline for more severe pneumococcal infections. [34][35][36][37] In our study, the prevalence of pneumonia in subjects tested during wave 1 was 23% overall, but 36% in Q fever positive subjects, which is higher than the 27% rate found in Q fever positive patients from a large 26-year cohort of patients with Q fever from the French National Reference Center for Q fever. [38] Nevertheless, a huge majority of patients in our study had no suspicion of pneumonia and would have had potential bene t from symptom-based exclusion of Q fever.…”
Section: Discussionmentioning
confidence: 79%